Bladder Cancer Diagnosis, Therapeutics, and Management - Lee, Cheryl T.; Wood, David P.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
In Bladder Cancer: Moving the Field Forward, Cheryl Lee, David Wood, and a panel of leading authorities and researchers provide a comprehensive review of the related literature, while providing insights into the obstacles of improved survival and discuss methods to advance the field of Bladder Cancer care. Their work aims to spur innovative thoughts and approaches to common problems in the management of early stage and advanced disease. The book discusses at length the state of bladder cancer staging and the optimal treatment for localized disease. Additional sections review the applications of existing systemic therapies and look at the infrastructure needed to support translational research efforts. Groundbreaking and authoritative, Bladder Cancer: Moving the Field Forward, is the definitive text on the current state of bladder cancer care and a must have for all urologists and medical oncologists who wish to provide their patients with the most comprehensive care.
Improving Bladder Cancer Staging -- Approaches to Carcinoma In Situ (CIS) -- Fluorescence Cytoscopy -- Restaging TURBT -- Understaging T2: Limitations of Pelvic Imaging -- MRI Endorectal Coil -- PET Imaging: Advances in the Detection of Locally Advanced and Nodal Disease -- Detection of Extravesical Disease: A Lack of Bladder Cancer Markers -- Identification of Nodal Metastases: The role of Iron Oxide Enhanced MRI -- Presence and Significance of Micrometastases -- Optimizing Treatment of Localized Disease -- Perioperative Intravesical Therapy -- BCG Refractory Disease -- Beyond BCG: Gemcitabine -- Beyond BCG: Taxanes -- Extended Lymph Node Dissection -- Prostate Capsule Sparing Cystectomy -- Preservation of Reproductive Organs in Women -- Nerve Sparing Radical Cystectomy -- Quality of Care Indicators for Radical Cystectomy -- Continent Diversion: QOL of Orthotopic Diversion vs. Ileal Conduit -- Voiding Dysfunction After Orthotopic Diversion -- Overcoming the Stigma of Complications of Continent Cutaneous Diversion -- Locally Advanced / Distant Disease: Multi-Modality Treatment -- Neoadjuvant Chemotherapy: The New Standard -- Adjuvant Chemotherapy in Bladder Cancer: A Good Concept But Where$1 (Bs the Proof? -- Beyond MVAC: New and Improved Chemotherapeutics -- Next Steps: Translational Research -- The Role of Microarray Technologies in Bladder Cancer Management -- Molecular Pathogenesis of Urothelial Carcinoma and the Development of Novel Therapeutic Strategies -- Tools for Study: National Databanking -- Vaccine Development -- Advances in Gene Therapy for Bladder Cancer.s
Keywords: Medicine; Urology; Medicine & Public Health; Urology/Andrology.